A multi-agent-based approach to dynamic scheduling and control for a flexible assembly line system - Vatankhah Barenji, Ali; Hashemipour, Majid (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
The success of a flexible assembly manufacturing system depends on efficacious production scheduling and control. Current assembly manufacturing scheduling and control algorithms lack the flexibility and reconfiguration abilities to manage disturbances when they occur. Consequently, system performance worsens quickly when the operation of the system is interrupted. The objective of this research was to examine whether the performance of a flexible assembly line system can be enhanced by implementing a radio frequency identification-based multi-agent distributed (RFIDMAD) scheduling and control system. A multi-agent manufacturing scheduling model was developed and implemented in a flexible assembly manufacturing system using a simulation model. Several measures of the performance of the system were considered in the simulation analysis. The simulation results indicate that an RFIDMAD scheduling and control system can increase the uptime productivity and production rate of an assembly manufacturing system.